Job task analysis of academic librarians assigned in the user services in Pampanga - Marzan, Michelle S.; Gonzales, Grace Marie B.; Ramos, Marian S.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
Task analysis is a systematic breakdown of a task into its elements. These elements include a detailed task description of both manual and mental activities tasks and element duration, task frequency, task allocation, task complexity, environmental condition, necessary equipment, and any other unique factors involved in or required for one or more humans to perform a given task. The purpose of task analysis is to describe a job as it is actually performed and to understand the job well enough to reliably and accurately define worker requirements. Task analysis is done in many fields such as education, allied medical profession, and engineering, including library science.
The primary objective of the study was to find out the current tasks performed by academic librarians assigned to the user services area in Pampanga. The study further determined the knowledge and skills employed by the respondents in performing the assigned tasks related to user services; and how do respondents perform the assigned tasks.
The study used the descriptive method of research. The questionnaire was used as the primary tool in gathering data along with ocular inspection and personal interviews to ascertain what tasks respondents actually perform.
Eighteen academic librarians from two universities in Pampanga were the respondents of the study. The findings revealed that checking in and out of library materials, answering reference queries, and providing bibliographic services are the most frequently performed tasks by the respondents assigned in the user services area. Likewise, the findings revealed that all respondents believed to possess a proficiency in searching information through the use of OPAC and ability to interpret information displayed on screen.
Results further showed that few respondents thought of critical thinking as important in most of the given tasks related to user services. Respondents perceived themselves to have a poor level of critical thinking skills. Likewise, they rated themselves to have poor knowledge regarding other library websites' structure and contents and knowledge of other library's circulation policy and procedures. Moreover, academic librarians use the computer in most of their tasks or activities.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic librarians -- Phillippines -- Pampanga; Librarians -- Pampanga -- Job descriptions